An Exploration of Adaptive Social Safety Nets Parameters in Malaysia: A Concept Paper - Ahmad Basri, Nur Ain Nabilah; Siti Hajar Abu Bakar Ah; Noralina Omar; Siti Nur Edlyn Nadia Zuraiju; Mahazril ‘Aini Yaacob; Nur Annizah Ishak; Mohd Alif Jasni (The Malaysian Journal of Social Administration, 2025)
This concept paper explores the critical parameters of adaptive social safety-net in the context of low-income households in Malaysia. The concept of adaptive social safety-net is derived and introduced by the World Bank in which it seeks to enhance the household resilience. Recent events such as the pandemic Covid-19 crises and increasing covariate shock happened shows that there is a gap and limitation in our social safety- net system particularly on how the Government’s efficiency as well as other authorities managing, funding the systems. Hence, reassess and strengthen current social protection mechanisms by integrating adaptive features that are responsive to local vulnerabilities. Using a quantitative approach, data will be collected through systematic random sampling among residents of Program Perumahan Rakyat (PPR) in Kuala Lumpur. The findings are expected to explore the critical parameters of an adaptive social safety-net to development of a more resilient and inclusive social protection framework that better supports low-income households during unforeseen shocks and contributes to long-term socioeconomic stability.